Make in India and Sustainable Industrial Development - Singh, Naib (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2016)
Indian economy is attaining the development at very rapid rate. India has the position as one of the fastest developing nation with higher Gross Domestic Products (GDP). Industries of India are contributing towards the GDP up to 28 percent. Industrial Policy is the main factor for the rapid development of the economy. Developing countries require any definite industrial supportive measure for combating many evils which are affecting the development adversely. For the sustainable development of the industrial sector we have to maintain as well as increase this share by adopting the supportive measures like ‘Make in India’. This Campaign will help the industrialists to think of ways by which indigenous products will not only fulfill the domestic demand but also give the boost to exports.